Is air pollution one of the risk factors for sudden deafness? Review of the literature - Magdalena Miłek; Mariola Banach; Angelika Foryś; Weronika Kmiotek; Zuzanna Kotowicz; Ksenia Kwaśniak; Agata Magierska; Anna Niemczyk; Weronika Stawska; Monika Ślusarczyk (Nicolaus Copernicus University in Toruń, 2024)
Introduction and objective: Sudden deafness is a serious clinical manifestation characterised by rapidly progressive hearing loss. As the duration of the disease process increases, hearing loss increases, so it is important to diagnose and begin treatment as early as possible. This paper aims to summarise the current state of knowledge on the main risk factors for sudden hearing loss and treatment methods, and the impact of environmental pollution on sudden hearing loss. Brief description of the state of knowledge: Sudden hearing loss, also known as sudden sensorineural hearing loss, refers to a sudden and significant deterioration of hearing. According to current medical knowledge, risk factors for sudden deafness mainly include microvascular disorders, autoimmune diseases, damage to the cochlear membrane and viral infections. According to some researchers, air pollution may contribute to sudden hearing loss; however, data are still lacking and there is a need for further research. Treatment of hearing loss can include medication, hyperbaric therapy, hearing aids and, in the most difficult cases, cochlear implants. Sudden deafness is a health problem with a significant impact on patients' quality of life. Understanding the causes, diagnosis and effective treatment are key to improving quality of life and social and occupational functioning. Methods and results: Literature review was performed using the PUBMED online database and Google Scholar. Summary: Hearing loss is a common condition that can have a variety of causes and dangerous consequences. This article discusses the causes of sudden hearing loss and available treatments. The need for further research into the treatment and rehabilitation of people with hearing loss to ensure the best possible quality of life and to improve social and occupational functioning is highlighted.